Assimilation or integration: Similarities and differences between acculturation attitudes of migrants from Central Asia and Russians in Central Russia - Lebedeva, Nadezhda M.; Tatiana A., Ryabichenko (Psychology in Russia : state of the art, 2016)
This paper is dedicated to the cultural specificities of three typical collective groups with respect to the representation of love. The research subject focuses on the cross-cultural similarities and differences in how love is conceptualized among highly educated citizens of Brazil (50), Russia (50), and Central Africa (50) (age range 21-60; M = 34). We used "The Classical ideas of love: acceptance and distancing" questionnaire (I.A. Djidaryan, E.V. Belovol, & O.V. Maslova) and the "Directed associations with 'love' as the wordstimulus" technique (on the basis of C.G. Jung's associative experiment and P. Vergès's methodology). The results show similarities and differences in how love is represented among the groups. The following similarities were found: Love is seen as all that is good and kind about a person, a way to become better. At the peripheral level, the social representation of love includes friendship, patience, and passion. At the point of cross-cultural differences, it was found that: a) The main emotion reflecting how love is represented for Brazilians is honesty, for Russians -- suffering, for Central Africans -- tenderness; b) Brazilians understand love as a sensual, personal moral choice; Russians perceive love as an obstacle, a problem in itself; Central Africans conceptualize love as God-given and ennobling of the person; c) love is conceptualized as something inherent and family-oriented among Russians, intrapersonal and intimate among Brazilians, and divine among Central Africans. The results mean that within peripheral confines, the notion of love among the groups matches to a certain extent R. Sternberg's triangle of love, while its core zone is culturally specific.